Smartphone Voice Calls Provide Early Biomarkers of Parkinsonism in Rapid Eye Movement Sleep Behavior Disorder - Illner, Vojtěch; Novotný, Michal; Kouba, Tomáš; Tykalová, Tereza; Šimek, Michal; Sovka, Pavel; Švihlík, Jan; Růžička, Evžen; Šonka, Karel; Dušek, Petr; Rusz, Jan (Movement disorders, 2024)
BACKGROUND: Speech dysfunction represents one of the initial motor manifestations to develop in Parkinson's disease (PD) and is measurable through smartphone. OBJECTIVE: The aim was to develop a fully automated and noise-resistant smartphone-based system that can unobtrusively screen for prodromal parkinsonian speech disorder in subjects with isolated rapid eye movement sleep behavior disorder (iRBD) in a real-world scenario. METHODS: This cross-sectional study assessed regular, everyday voice call data from individuals with iRBD compared to early PD patients and healthy controls via a developed smartphone application. The participants also performed an active, regular reading of a short passage on their smartphone. Smartphone data were continuously collected for up to 3 months after the standard in-person assessments at the clinic. RESULTS: A total of 3525 calls that led to 5990 minutes of preprocessed speech were extracted from 72 participants, comprising 21 iRBD patients, 26 PD patients, and 25 controls. With a high area under the curve of 0.85 between iRBD patients and controls, the combination of passive and active smartphone data provided a comparable or even more sensitive evaluation than laboratory examination using a high-quality microphone. The most sensitive features to induce prodromal neurodegeneration in iRBD included imprecise vowel articulation during phone calls (P = 0.03) and monopitch in reading (P = 0.05). Eighteen minutes of speech corresponding to approximately nine calls was sufficient to obtain the best sensitivity for the screening. CONCLUSION: We consider the developed tool widely applicable to deep longitudinal digital phenotyping data with future applications in neuroprotective trials, deep brain stimulation optimization, neuropsychiatry, speech therapy, population screening, and beyond. © 2024 The Author(s). Movement Disorders published by Wiley Periodicals LLC on behalf of International Parkinson and Movement Disorder Society.
Keywords: Speech Disorders; porucha chování v REM spánku; Humans; lidé středního věku; prodromální symptomy; Prodromal Symptoms; Female; Aged; REM Sleep Behavior Disorder; chytrý telefon; senioři; lidé; Biomarkers; hlas; ženské pohlaví; biologické markery; Male; Parkinsonian Disorders; Middle Aged; Smartphone; poruchy řeči; Voice; Cross-Sectional Studies; parkinsonské poruchy; mužské pohlaví; Parkinson Disease; průřezové studie; Parkinsonova nemoc